Money Matters: The Power of Financial Literacy on University Student Spending Decisions - Daisy Mui Hung Kee; See Thor Hong Xuan; Seow Hui Yi; Shahredzuan Bin Itnes; Shakty Sanjeetha Varma A/p Saseetharan; Dehao Shu (Asia Pacific Journal of Management and Education (APJME), 2025)
As university students navigate the transition to financial independence, they face a new set of challenges in managing limited resources. Financial literacy becomes essential to making informed decisions about budgeting, saving, and spending. This study explores the impact of financial literacy on university students’ spending decisions, examining how key factors such as financial education, social media exposure, and peer influence shape their financial behaviors. With increasing access to financial products and services, young adults are confronted with complex financial choices that require a solid understanding of financial principles. However, without sufficient financial literacy, students are at risk of poor financial decision-making, debt accumulation, and financial insecurity. Using a survey of 150 university students, the findings highlight the significant role of financial literacy and financial behavior as a mediator, with financial education, social media exposure, and peer influence directly impacting financial literacy and behavior. Notably, financial behavior and financial literacy significantly predict financial decision-making, emphasizing the need for targeted interventions. The findings reveal the importance of equipping students with practical financial education programs and tools that enhance literacy and enhance informed decision-making.